The Effect of Exogenous Bile Acids on Antioxidant Status and Gut Microbiota in Heat-Stressed Broiler Chickens - Yin, Chang; Xia, Bing; Tang, Shanlong; Cao, Aizhi; Liu, Lei; Zhong, Ruqing; Chen, Liang; Zhang, Hongfu (Frontiers in Nutrition, 2021)
Bile acids are critical for lipid absorption, however, their new roles in maintaining or regulating systemic metabolism are irreplaceable. The negative impacts of heat stress (HS) on growth performance, lipid metabolism, and antioxidant status have been reported, but it remains unknown whether the bile acids (BA) composition of broiler chickens can be affected by HS. Therefore, this study aimed to investigate the modulating effects of the environment (HS) and whether dietary BA supplementation can benefit heat-stressed broiler chickens. A total of 216 Arbor Acres broilers were selected with a bodyweight approach average and treated with thermal neutral (TN), HS (32°C), or HS-BA (200 mg/kg BA supplementation) from 21 to 42 days. The results showed that an increase in average daily gain (P < 0.05) while GSH-Px activities (P < 0.05) in both serum and liver were restored to the normal range were observed in the HS-BA group. HS caused a drop in the primary BA (P = 0.084, 38.46%) and Tauro-conjugated BA (33.49%) in the ileum, meanwhile, the secondary BA in the liver and cecum were lower by 36.88 and 39.45% respectively. Notably, results were consistent that SBA levels were significantly increased in the serum (3-fold, P = 0.0003) and the ileum (24.89-fold, P < 0.0001). Among them, TUDCA levels (P < 0.01) were included. Besides, BA supplementation indeed increased significantly TUDCA (P = 0.0154) and THDCA (P = 0.0003) levels in the liver, while ileal TDCA (P = 0.0307), TLCA (P = 0.0453), HDCA (P = 0.0018), and THDCA (P = 0.0002) levels were also increased. Intestinal morphology of ileum was observed by hematoxylin and eosin (H&E) staining, birds fed with BA supplementation reduced (P = 0.0431) crypt depth, and the ratio of villous height to crypt depth trended higher (P = 0.0539) under the heat exposure. Quantitative RT-PCR showed that dietary supplementation with BA resulted in upregulation of FXR (P = 0.0369), ASBT (P = 0.0154), and Keap-1 (P = 0.0104) while downregulation of iNOS (P = 0.0399) expression in ileum. Moreover, 16S rRNA gene sequencing analysis and relevance networks revealed that HS-derived changes in gut microbiota and BA metabolites of broilers may affect their resistance to HS. Thus, BA supplementation can benefit broiler chickens during high ambient temperatures, serving as a new nutritional strategy against heat stress.